Ultrahigh purity beta gallium oxide microstructures. Issue 17 (1st September 2022) - Suárez, M.; Arias, A.; Castillo-Saenz, J.R.; Curiel-Alvarez, M.; Pérez-Landeros, O.; Mateos, D.; Martínez-Guerra, E.; Concha-Balderrama, A.; Valdez-Salas, B.; Nedev, N.
Abstract: Ultrahigh purity gallium oxide (Ga2 O3 ) microstructures were synthesized via hydrothermal method using gallium nitrate hydrate and ammonium hydroxide to synthesize gallium hydroxide, followed by calcination at a 1000 °C. Scanning electron microscopy revealed that following calcination, the material showed a large number of microparticles with lengths of ≤1 μm and diameters of 250–350 nm. Energy-dispersive X-ray spectroscopy, X-ray diffraction, Raman spectroscopy, infrared spectroscopy, and X-ray photoelectron spectroscopy analyses indicated the high purity and near-stoichiometric composition of the material. The results also confirm the formation of β-phase Ga2 O3 with high crystallinity.